2010
DOI: 10.1016/b978-0-12-380995-7.00004-5
|View full text |Cite
|
Sign up to set email alerts
|

How Tolerogenic Dendritic Cells Induce Regulatory T Cells

Abstract: Since their discovery by Steinman and Cohn in 1973, dendritic cells (DCs) have become increasingly recognized for their crucial role as regulators of innate and adaptive immunity. DCs are exquisitely adept at acquiring, processing and presenting antigens to T cells. They also adjust the context (and hence the outcome) of antigen presentation in response to a plethora of environmental inputs that signal the occurence of pathogens or tissue damage. Such signals generally boost DC maturation, which promotes their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
392
1
8

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 460 publications
(416 citation statements)
references
References 359 publications
10
392
1
8
Order By: Relevance
“…The tolerogenic nanoparticle (SVP) are made with a polymer, PLGA, that is biocompatible, biodegradable and used in multiple products licensed for clinical use by regulatory agencies [28]. We have combined it with an immunomodulatory agent, rapamycin, which has been validated in humans and is capable of facilitating tolerance [10,20,21,29,30]. The delivery of rapamycin by nanoparticles allows for efficient transport to lymphoid organs and capture by phagocytic antigen presenting cells (APCs) [20], and thus reduce non-specific toxicity through chronic systemic administration.…”
Section: Svp Approach For Fviii Immune Tolerancementioning
confidence: 99%
See 2 more Smart Citations
“…The tolerogenic nanoparticle (SVP) are made with a polymer, PLGA, that is biocompatible, biodegradable and used in multiple products licensed for clinical use by regulatory agencies [28]. We have combined it with an immunomodulatory agent, rapamycin, which has been validated in humans and is capable of facilitating tolerance [10,20,21,29,30]. The delivery of rapamycin by nanoparticles allows for efficient transport to lymphoid organs and capture by phagocytic antigen presenting cells (APCs) [20], and thus reduce non-specific toxicity through chronic systemic administration.…”
Section: Svp Approach For Fviii Immune Tolerancementioning
confidence: 99%
“…Strategies to induce tolerance include conjugating antigen to splenocytes [8], immature dendritic cells (DC) [9,10], or synthetic microparticles [11,12], oral tolerance [13], gene therapy [14] or co-treatment with immunosuppressive drugs, such as methotrexate [15]. Recently, it has been reported that systemic co-administration of rapamycin, a immunosuppressant drug commonly used to prevent transplant rejection, prevented immune response and induced tolerance to FIX and FVIII in mouse models of hemophilia A and B, respectively [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Characteristic features of DC differentiation or "maturation" include a transient increase in phagocytosis and macropinocytosis for efficient antigen uptake, increased surface expression of costimulatory molecules (e.g., CD86, CD80, CD40), and enhanced potential to migrate from peripheral tissues to the local lymphoid tissues for interaction with T cells (West et al 2004; Reis e Sousa 2006). Several other stimuli, for example, TNF-a, can drive alternative DC maturation programs that result in tolerogenic rather than immunogenic DCs (Menges et al 2002;Tan and O'Neill 2005;Cools et al 2007;Maldonado and von Andrian 2010).…”
mentioning
confidence: 99%
“…The depletion of Tregs in a genetic model resulted in spontaneous clearance of the infection (9) and greatly improved the efficacy of an H. pylori vaccine (10). H. pylori-induced Tregs differentiate in the periphery as a result of their priming by tolerogenic DCs (13), which convert naive T cells into FoxP3 + Tregs through antigen presentation in the absence of costimulatory signals or cytokines (13,14). We have shown recently that H. pylori exposure reprograms DCs toward a tolerance-promoting phenotype in vitro and in vivo; H. pyloriexperienced DCs fail to induce T-cell effector functions, but rather acquire the ability to induce FoxP3 and CD25 expression in cocultured naive T cells (12).…”
mentioning
confidence: 99%